HUBUNGAN KELINCAHAN, KECEPATAN DAN JUGGLING TERHADAP KETERAMPILAN DRIBBLE FUTSAL - Akbari, Wahyu; Hidasari, Fitriana Puspa; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem discussed in this study is how agility, speed and juggling of the futsal dribble skills of futsal extracurricular participants in SMAN 3 Pontianak. The purpose of this study was to determine the relationship of agility, speed and juggling of the futsal dribble skils of futsal extracurricular participants of SMAN 3 Pontianak. The method used in this research is quantitative descriptive method, which is a survey method with collaborative techniques, research using this method aims to determine the relationship of agility, speed and juggling of futsal dribble skills in futsal extracurricular participants of SMAN 3 Pontianak. With a sample size of 20 people. This research technique uses tests and measurements, with a grating instrument measuring agility, speed and juggling of futsal dribble skills. Data analysis uses correlation. From the analysis of data obtained manually, it can be concluded that in general there is a significant relationship between agility, speed and juggling of futsal dribble skills in futsal extracurricular participants of SMAN 3 Pontianak. With the results of the analysis of the multiple correlation coefficient R between agility, speed and juggling ability to the results of the ability of dribble is R of 0,851. Keywords: Agility, Speed, Juggling and Dribble Abilities.